A articulação entre política externa e política de defesa no Brasil: uma Grande Estratégia inconclusa - Lima, Raphael Camargo [UNESP] (2015)
The purpose of this dissertation is to analyze the relationship between the foreign and defence policies in Brazil under Lula and Rousseff administrations, between 2003 and 2013. We considered the political process underlying this relationship to be too complex to be covered by only a single prism. Therefore, we sought to analyze it through one case study and three major dimensions: external action, institutions and ideas. We worked with the hypothesis that the relationship between the two policies has been an unconcluded Grand Strategy. This condition indicates that there was increasing convergence during the period, although Brazil has not reached the level where both are treated jointly - namely, considered as complementary and combinable means to achieve the country's international goals. We intended to demonstrate that the background of this rapprochement between these two policies was a confluence of world views and expectations towards Brazilian international insertion by several groups, which also affected, and was affected by, institutional tensions and a gradual increase in Brazilian Ministry of Defence international profile. Overall, these joint processes have increased the complexity of the dynamics between foreign and defence policies in the country - a result of pluralization of stakeholders, organizational reform and expansion of international actions of Brazil in the defense sector. Nonetheless, the country was still not able to institutionalize a Grand Strategy throughout its main institutions responsible for external action